Jawther Al-Saqlabi was influential in the Fatimid state in the Maghreb (Journal of the College of Basic Education, 2024)
Biographies and biographies are among the important historical sources that conveyed to us accurate information about personalities who had a great influence on the course of Islamic history, including the book The Biography of Professor Jawther by Abu Ali Al-Jawthari, which is one of the biographical books that conveyed accurate details about an important and influential figure in the history of the Fatimid state, and this influence is conveyed by him. Through sincerity and dedication to the service of the Fatimid imams in the ideological and administrative aspects, his loyalty to them was rare to the point that they considered him one of them despite his foreignness and slavery, but he obtained the rank of minister in the East and was closer to it because of his efforts in building the Fatimid state in Morocco. This book did not only narrate to us the biography of Jawdhar, but it presented a detailed historical account of the march of the Fatimid state in Morocco in its military aspect and provided details that were not provided to us by the historians of this state. It is a gratitude to Jawdhar on the part of the author of the book, Abu Ali Al-Mansouri Al-Jawthari, who would not have been known without his book.